PIGG defines the Emm blood group system - William J. Lane (Nature Portfolio, 2021)
Abstract Emm is a high incidence red cell antigen with eight previously reported Emm− probands. Anti-Emm appears to be naturally occurring yet responsible for a clinically significant acute hemolytic transfusion reaction. Previous work suggests that Emm is located on a GPI-anchored protein, but the antigenic epitope and genetic basis have been elusive. We investigated samples from a South Asian Indian family with two Emm− brothers by whole genome sequencing (WGS). Additionally, samples from four unrelated Emm− individuals were investigated for variants in the candidate gene. Filtering for homozygous variants found in the Emm− brothers and by gnomAD frequency of < 0.001 resulted in 1818 variants with one of high impact; a 2-bp deletion causing a frameshift and premature stop codon in PIGG [NM_001127178.3:c.2624_2625delTA, p.(Leu875*), rs771819481]. PIGG encodes for a transferase, GPI-ethanolaminephosphate transferase II, which adds ethanolamine phosphate (EtNP) to the second mannose in a GPI-anchor. The four additional unrelated Emm− individuals had various PIGG mutations; deletion of Exons 2–3, deletion of Exons 7–9, insertion/deletion (indel) in Exon 3, and new stop codon in Exon 5. The Emm− phenotype is associated with a rare deficiency of PIGG, potentially defining a new Emm blood group system composed of EtNP bound to mannose, part of the GPI-anchor. The results are consistent with the known PI-linked association of the Emm antigen, and may explain the production of the antibody in the absence of RBC transfusion. Any association with neurologic phenotypes requires further research.